5-HT7 Receptor Restrains 5-HT–induced 5-HT2A Mediated Contraction in the Isolated Abdominal Vena Cava. Issue 2 (August 2021) - Gonzalez-Pons, Romina; McRae, Kiera; Thompson, Janice M.; Watts, Stephanie W.
Abstract : Abstract: Although discovered as a vasoconstrictor, 5-hydroxytryptamine (5-HT, serotonin) infused into man and rodent reduces blood pressure. This occurs primarily through activation of 5-HT7 receptors and, at least in part, venodilation. Vascular mechanisms by which this could occur include direct receptor activation leading to vasodilation and/or suppression of contractile 5-HT receptor activation. This study tests the hypothesis that the 5-HT7 receptor restrains activation of the 5-HT2A receptor. A subhypothesis is whether agonist-induced activation—independent of constitutive activity—of the 5-HT7 receptor is necessary for this restraint. The isolated abdominal aorta and vena cava from the normal male Sprague–Dawley rat was our model. Studies used real-time PCR and a pharmacological approach in the isolated tissue bath for measurement of isometric tone. Although 5-HT2A receptor mRNA expression in both aorta and vena cava was significantly larger than that of the 5-HT7 receptor mRNA, the 5-HT7 /5-HT2A receptor mRNA ratio was greater in the vena cava (0.30) than in the aorta (0.067). 5-HT7 receptor antagonism by SB266970 and DR 4458 increased maximum contraction to 5-HT in the isolated vein by over 50% versus control. The 5-HT2A receptor agonists TCB-2 and NBOH were more potent in the aorta compared with 5-HT but less efficacious, serving as partial agonists. By contrast, these same three agonists caused no contraction in the vena cava isolated from the same rats up to 10 μM agonist. Antagonism of the 5-HT7 receptor by SB269970 did not increase either the potency or efficacy of TCB-2 or NBOH. These data support that the 5-HT7 receptor itself needs to be stimulated to reduce contraction and suggest there is little constitutive activity of the 5-HT7 receptor in the isolate abdominal vena cava.